Riscos e benefícios das terapias trombolíticas, antiagregantes plaquetárias e anticoagulantes nas síndromes coronarianas agudas com supradesnivelamento do segmento st: revisão sistemática - Bruno Ramos Nascimento (2011)
Introduction: Acute myocardial infarction with ST-segment elevation (STEMI) is responsible for high morbidity and mortality, and new classes of drugs are being progressively added to its treatment overtime. The real benefit versus the bleeding risk of the associations is not yet known, given the diversity of regimens and doses tested in the large trials. Objectives: To assess, by systematic review, the impact of the progressive addition of thrombolytics, anticoagulants, antiplatelets and primary angioplasty on clinical outcomes: death, reinfarction and major bleeding in patients with STEMI, and the temporal evolution of these outcomes. Methods: We conducted a search in the Pubmed databasewith the words "acute," "myocardial infarction / therapy", to identify randomized trials in English or Spanish involving adult humans with STEMI, with at least 500 patients, comparing classes of drugs: thrombolytics, antiplatelet agents and anticoagulants. The study should provide the death, reinfarction and major bleeding rates. The arms withsimilar characteristics were grouped, and was evaluated correlation between progressive addition of drugs, number of drugs and primary angioplasty and these outcomes by Spearman coefficient and multivariate regression. Was also performed and the correlation between the year and the era of the study and the incidence of the outcomes. Results: The search resulted in 2313 articles, with 59 studies remaining after exclusions, and a total of 404,556 patients, with mean follow up time of 23,3 days, were divided into 35 groups of treatment arms. Evaluating the gradual introduction of drugs (12 groups), there was a trend towards the correlation with death (r = -0.564, p = 0.056) and major bleeding (r = 0.571, p = 0.053). There was a statistically significant correlation between the number of drugs and the rates of death (r = -0.466, p = 0.005) and bleeding (r = 0.403, p = 0.016), which was confirmed in a multivariate regression model. The year of the study had significant correlation with th e 3 outcomes assessed: death (r = -0.380, <0.001), bleeding (r = 0.212, p = 0.014) and reinfarction (r = -0.231, p = 0.009), as well as the era of accomplishment. Conclusion: With the increasing complexity of the pharmacological treatment of STEMI, there is significant reduction in mortality, accompanied by an increased rate of bleeding that does not nullify the net clinical benefit. There is a correlation between the year and the age of the study and reduction of mortality and reinfarction, with a concomitant increase in bleeding complications